Clarity of Diagnosis Writing and Accuracy of Coding in Heart Failure Based on ICD-10 at Hospital X: Kejelasan Penulisan Diagnosa dan Keakuratan Kodefikasi pada Heart Failure Berdasarkan ICD-10 di Rumah Sakit X - Harmanto, Deno; Budiarti, Anggia; Rahayu, Dinda Sri (Procedia of Engineering and Life Science, 2025)
It is very important to code the diagnosis of Heart Failure correctly and accurately, inaccuracies in codes are often found in medical record files such as unclear writing of the diagnosis or even incomplete supporting documents and the absence of a 4th character code in the diagnosis of Heart Failure. If coding is not carried out accurately, it will result in errors in disease recording indexes and actions, inaccurate report information data and inaccurate INA-CBG rates. The purpose of this study aims to determine the clarity of writing diagnoses and the accuracy of heart failure coding based on ICD-10 at Rafflesia Hospital, Bengkulu. The type of research is descriptive. The data used are primary data and secondary data which are processed univariately, data collection methods are through interviews and observation. The tool used is a checklist sheet with direct observation of 176 medical record files for the diagnosis of heart disease. Of the 176 medical record files for the diagnosis of Heart Failure, there is clarity in writing the diagnosis on the medical resume, a small number of 56 files (32%) are clear, but the majority of 120 files (68%) are unclear and the accuracy of codes based on ICD-10 is mostly 64 files (36% ) were accurate and as many as 112 files (64%) were inaccurate.